Effect of Dietary Levels of Processed Leucaena leucocephala Seeds on Broiler Performance and Blood Parameters - Ahmed, Mohamed Elamin; Abdelati, Khadiga Abbas (International Journal of Poultry Science, 2008)
In the current experiment, Leucaena leucocephala seeds were subjected to three treatments (soaking, roasting and supplementation with 40mg/Kg ferrous oxide). Then treated and untreated leucaena seeds were incorporated in boiler diets at 0, 6 and 12%. Soaking and roasting of the seeds reduced phytate, whereas tannin was not significantly affected. Feed intake and weight gain were significantly (p ≤ 0.05) reduced with the inclusion of 12% untreated leucaena seed, 12% soaked or 12% roasted leucaena seeds. However, feeding diets that supplemented with ferrous had no negative effect on feed intake and weight gain compared with control. Dietary treatments did not affect haematological parameters, plasma GOT ALP, K, inorganic phosphorus (Pi), total protein, albumin, globulin, cholesterol, uric acid and tibia P. Plasma glucose for birds fed leucaena seed diets was not significantly different as compared with those fed the control diet.